Vasoactive intestinal peptide (VIP) differentially affects inflammatory immune responses in human monocytes infected with viable Salmonella or stimulated with LPS - Askar, Basim Ali; Ibrahim, Hiba; Barrow, Paul; Foster, Neil (Elsevier, 2015)
We compared the effect of VIP on human blood monocytes infected with Salmonella typhimurium 4/74 or stimulated with LPS. VIP (10−7 M) increased monocyte viability by 24% and 9% when cultured for 24 h with 4/74 or Salmonella LPS (100 ng/ml), respectively. Significantly increased (P < 0.05) numbers of 4/74 were also recovered from monocytes co-cultured with VIP after 6 h post-infection (pi) and this remained high after 24 h pi. Both 4/74 and LPS increased (P < 0.05) the concentration of TNF-α, IL-1β and IL-6 measured in monocyte supernatants. However, LPS induced this effect more rapidly while, with the exception of IL-6, 4/74 induced higher concentrations (P < 0.05). VIP significantly decreased (P < 0.05) TNF-α and IL-1β production by 4/74-infected monocytes after 6 pi, but only after 24 h in LPS-cultured monocytes. This trend was reversed for IL-6 production. However, TNF-α and IL-1β production by 4/74-infected monocytes, cultured with VIP, still remained higher (P < 0.05) than concentrations measured in supernatants cultured only with LPS. VIP also increased (P < 0.05) production of anti-inflammatory IL-10 in both 4/74 and LPS cultures after 24 h. We also show a differential effect of VIP on the expression of TNFα and IL-6 receptors, since VIP was only able to decreased expression in LPS-stimulated monocytes but not in 4/74-infected monocytes.